How do you simplify (x^(3/2))/(3/2)?
1 Answer
Feb 16, 2016
Explanation:
The most important thing to know here is that dividing by a fraction is equivalent to multiplying by the fraction's reciprocal.
The expression we have here can be written as:
=x^(3/2)-:3/2
Instead of dividing by the fraction
=x^(3/2)xx2/3
This can be written as
=(2x^(3/2))/3
This is a fine simplification. However, if you want to simplify the fractional exponent, we can use the rule which states that
x^(a/b)=rootb(x^a)
Thus, the expression equals
=(2root2(x^3))/3=(2sqrt(x^3))/3
We could simplify
=(2xsqrtx)/3
This really becomes a matter of opinion as to where you wish to stop simplifying.